Shaped Charge Hydraulic Blasting: An Environmental, Safe, and Economical Method of Directional Roof Cutting. (13th March 2021) - Zhang, Quan; Wang, Jiong; Guo, Shan; Gong, Weili; Feng, Longfei; Wang, Haosen; Ming, Can; Ma, Zimin
Abstract : Shaped charge blasting (SCB)—a directional fracture blasting technology—has the disadvantages of low safety, harmful gas, and dust emissions. This study proposes a new type of directional rock-breaking technology called shaped charge hydraulic blasting (SCHB) that uses water as the blasting medium instead of air. To verify the effectiveness of the new method, we performed a theoretical analysis. Twelve groups of on-site directional roof-cutting tests were carried out on SCB and SCHB for comparison in a coal mine. The results showed that, although both blasting methods achieved the goal of directional roof cutting for noncoal pillar mining, SCHB had greater blasting power and produced 8% higher crack rate than SCB for the same charge amount. SCHB required 12.5% less charge than SCB when the crack rate was basically the same. SCHB effectively reduced the concentration of CO. The maximum concentration of CO was reduced by 22–62% compared with SCB. The maximum concentration decreased parabolically with the monitoring distance. In addition, water can absorb high temperature and inhibit sparks from blasting, so SCHB can prevent gas explosions. Therefore, SCHB is an environmental, safe, and economical method of directional roof cutting, which has wide applications in mining and geotechnical engineering.